Consumption Time of Captopril Influenced the Outcomes of Patients with Stage 1 Hypertension - Sulastri Herdaningsih; Ahmad Muhtadi; Keri Lestari (Universitas Padjadjaran, Indonesia)
Differences in drugs consumption time may affect its absorption and metabolism in the bodywhich could lead to differences in its efficacy. For hypertension patients, one of the mostfrequently used drugs for lowering blood is captopril. However, information regarding theinfluence of consumption time on captopril efficacy was limited. Therefore, this study wasconducted to compare the efficacy of captopril in lowering blood pressure when administeredbefore and after meal. This was an experimental study with two treatment groups,conducted at Dr. Soedarso General Hospital, Pontianak, Indonesia, during April-June 2015.Statistical analysis was performed using Mann-Whitney, Exact-Fisher, and T-test. We foundout that the reduction of systolic blood pressure in group who consumed captopril beforeand after meal was 30 mmHg and 25 mmHg, respectively (p<0.05). The similar reduction indiastolic bloos pressure was observed in both groups (10 mmHg, p>0.05). In conclusion, itis recommended to take captopril on an empty stomach since it showed better efficacy whenadministered before meal compared to after meal consumption.Keywords: hypertension, captopril, absorption